Temperament an important principle for health preservation in Tibb an-Nabawi and Unani-Tibb (Bangladesh Journal of Medical Science, 2017)
Many prominent Greco-Arab (Unani-Tibb) physicians contributed to the advancement of medicine with their observations, practice, experience and experiments which gave priority to the preservation of health over the curing of ailments. Tibb an-Nabawi (Prophetic Medicine), the foundation of Islamic medicine placed great emphasis on preventative measures relating to lifestyle incorporating the spiritual, emotional and physical aspects of man. The key component to linking mans inter-relationship with his environment was understood through the concept of temperament. This concept remains at the core of Unani-Tibb up until today in terms of research and practical application within the clinical setting. Central to the understanding of temperament are the associated qualities of heat, cold, moisture and dryness, the combination of which describes each individuals unique constitutional make-up including personality traits, physical appearances and disease predispositions. Historically this formed the basis to the understanding of pathology and up until today it continues to guide physicians on individualized treatment regimes. All classical references of Tibb an-Nabawi attribute the onset of illnesses to the disturbance or imbalance of ones temperament. This paper aims to shed light on the concept of temperament as explained in the classical texts of Tibb an-Nabawi and Unani-Tibb and its practical application for health promotion and disease prevention.Bangladesh Journal of Medical Science Vol.16(4) 2017 p.487-495